A rapid test to measure adhesion between optical fibers and ethylene–vinyl acetate copolymer (EVA). (July 2016) - Tomić, N.Z.; Međo, B.I.; Stojanović, D.B.; Radojević, V.J.; Rakin, M.P.; Jančić-Heinemann, R.M.; Aleksić, R.R.
Abstract: Optical fibers are transported on a drum and on some occasions it is essential to fix them and to keep them fixed to the drum. Adhesives are used in such situations to obtain the best and durable fixation. This research shows a new approach for the examination of the adhesion effects and forces between the optical fibers and the adhesive during a tensile test. A solution of ethylene–vinyl acetate (EVA) copolymer in toluene was used as the adhesive for optical fibers and applied using specially designed apparatus. The testing procedure consisted of optical fiber characterization using optical microscopy for measurement of geomertrical parameters; tensile test to obtain the strength of adhesion that keeps the fibers together; nanoindentation of the optical final layer; SEM for precise geometry measurements and insight in the adhesive aspect after the test, and FTIR analysis to find out the chemical composition of polymer protective coating to have an obtain information about chemical environment for the adhesive. The optical fiber with outstanding mechanical characteristics was used to examine adhesives. A sample of two fibers connected with EVA was subjected to the tensile test to examine the adhesion forces. Finite element modeling was used to simulate the behavior and stress distribution of the adhesion layer. This method could assist in reaching a conclusion about the quality of the adhesion obtained in an experimental procedure.